Achieving purely organic room temperature phosphorescence in aqueous solution. Issue 1 (12th July 2022) - Sun, Hao; Zhu, Liangliang
Abstract: Purely organic room temperature phosphorescence (RTP) materials have aroused increasing interests in recent years and have been widely applied in anti‐counterfeiting, biological imaging, sensing, etc. Currently, these materials can be efficiently developed in crystalline states and amorphous polymer‐doped systems. However, achieving organic RTP in solution, especially in water solution, is still a formidable challenge. Recently, reports on aqueous phase RTP have been increasing and some feasible design strategies have been proposed; however, related investigations are still limited and there is a lack of systematic reviews. Therefore, we summarized the recent cases of aqueous phase organic RTP emission with primarily focusing on the RTP properties and efficient design strategies (e.g., forming nanoparticles from phosphorescent molecules and macrocyclic supramolecular assembly). Moreover, promising applications of the aqueous phase organic RTP emission in bio‐imaging and sensing were discussed. Some detailed perspectives concerning materials design and application were provided with the hope to provide inspiration for the future development of aqueous phase organic RTP. Abstract : Graphical abstract. Purely organic room temperature phosphorescent (RTP) materials have aroused increasing interests; however, achieving aqueous phase organic RTP emission is still a formidable challenge. This review summarizes the recent advances of organic materials with RTP emission in aqueous solution, primarily focusing on the efficient design strategies and their promising applications in bio‐imaging and sensing, with the hope to provide inspiration for aqueous phase organic RTP materials.